When crime becomes law: legislative attacks on rural people's rights and nature in Brazil - Mitidiero Junior, Marco Antonio (Criminological encounters, 2022)
The aim of this text is to present and analyse political‒legislative actions of both the legislative and executive branches of government in the proposal of bills which signify retrogressions on the rights of rural men and women and on nature preservation, actions that have prompted us to propose the notion of ‘assault against the rural people’. We focus on the period 2016‒2020, the period surrounding the coup d’etat in Brazil, the 2018 election and the first year of an extreme right-wing government rallied around Jair Bolsonaro. The survey results show that the proposal of new bills of law in Brazil constitutes a type of violence which tends to legitimate environmental and social crime.